2014
DOI: 10.1186/1471-2458-14-1243
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life (QoL) assessment in a cohort of patients with Phenylketonuria

Abstract: BackgroundPhenylketonuria (PKU) is a chronic inborn error of amino acid metabolism that requires lifelong follow-up and intervention, which may represent strains on Quality of Life (QoL). This observational study evaluated QoL in a cohort of PKU patients, using updated and detailed instruments.Methods22 patients with mild PKU respondent to BH4 and 21 patients with classical PKU treated with diet were recruited in this study. Adult patients completed WHOQOL questionnaire-100 (WHOQOL-100) and pediatric patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 47 publications
4
40
3
1
Order By: Relevance
“…Elsewhere, the difference in physical and mental domain scores between patients and healthy controls was nonsignificant . Additionally, one study reported significantly lower QoL in male vs female patients, and in patients with lower educational level, despite a normal QoL score in the overall population …”
Section: Quality Of Lifementioning
confidence: 98%
See 1 more Smart Citation
“…Elsewhere, the difference in physical and mental domain scores between patients and healthy controls was nonsignificant . Additionally, one study reported significantly lower QoL in male vs female patients, and in patients with lower educational level, despite a normal QoL score in the overall population …”
Section: Quality Of Lifementioning
confidence: 98%
“…Several studies used standardized QoL tests, which reported good QoL in patients, comparable with that of healthy controls . However, specific QoL domains may be affected in adults with PKU, despite normal scores overall.…”
Section: Quality Of Lifementioning
confidence: 99%
“…15 Lower QOL scores in males with PKU and lower education rates have also been reported. 16 Individuals requiring craniomaxillofacial surgery differ from other chronic medical conditions given they cannot hide their physical appearance and can be subjected to ridicule and objectification, leaving them stigmatised and traumatised. 17 There are reports of lower satisfaction with their facial appearance, self-esteem issues and decreased quality of life in this patient group, 18 as well as depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…The diet therapy may affect many aspects of their daily life and quality of life (QoL), as well as of their family members'. In countries other than Japan, some studies have been conducted on the daily life and QoL of patients with IEM and of their parents (Lambert and Boneh 2004;Simon et al 2008;Stockler et al 2012;Cazzoria et al 2014). As one of the factors associated with their QoL, children with IEM in Turkey with bad diet compliance reportedly had lower scores in two aspects of QoL assessment: school labeling and perception of disease (Eminoglu et al 2013).…”
mentioning
confidence: 99%